The hedonistic calculus in the renaissance - Vilar, Mariano Alejandro (2017)
In his letters and maxims, Epicurus advises his readers to weigh each pleasure and pain since on occasion a small pain should be tolerated to obtain a greater pleasure, and a small pleasure should be avoided if it will bring a greater pain. This idea is commonly known as the “Epicurean calculus” or “hedonistic calculus.” In the Renaissance, the reappraisal of Epicurus implied rethinking the meaning of this calculus according to the parameters of Christian life. Lorenzo Valla’s De vero bono (1431) and Erasmus’ Epicureus (1533) show two different ways in which this measuring of pleasures and pain can be reinterpreted to fit new contexts and meanings. We will focus on the meaning that the calculus acquires when it includes heavenly pleasures and in the significance of utilitas in relation to the measuring of the advantageous or disadvantageous effects of our actions.